2017
DOI: 10.18388/abp.2017_1608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 4'-O-acetyl-isoxanthohumol and its analogues as antioxidant and antiproliferative agents

Abstract: Isoxanthohumol (2) and its 4'-O-monoacylated (3) and 7,4'-O-diacetylated (4) derivatives were synthesized and evaluated in vitro for their cytotoxic activity against several cancer cell lines of various origins: MCF-7 (breast), A549 (lung), MESSA (uterine sarcoma), LoVo (colon), drug-resistant human cancer cells (MESSA/DX and LoVo/DX), glioblastoma (U-118 MG), and also towards the non-cancerous cell line MCF-10A (normal breast cells). An antiproliferative assay indicates that 7,4'-di-O-acylisoxanthohumol (4) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Several derivatives were also isolated from Moraceae [16,20,[37][38][39], Asteraceae [24] and Cannabaceae [12][13][14] families. A great number of prenylated flavanones were collected from propolis of different origins [47,48] and some of them were obtained by synthesis [12,14,49] (compounds 77-118, Table 4).…”
Section: And Figures 4-6) a Few Examples From Fabaceaementioning
confidence: 99%
“…Several derivatives were also isolated from Moraceae [16,20,[37][38][39], Asteraceae [24] and Cannabaceae [12][13][14] families. A great number of prenylated flavanones were collected from propolis of different origins [47,48] and some of them were obtained by synthesis [12,14,49] (compounds 77-118, Table 4).…”
Section: And Figures 4-6) a Few Examples From Fabaceaementioning
confidence: 99%
“…According to Bocquet et al, it was possible to demonstrate that desmethylxanthohumol in H. lupulus has antifungal activity against Zymoseptoria tritici (MIC value of 0.63 g/L) [42]. Additionally, it was found that xanthohumol can inhibit the growth of three Fusarium species, with MIC values from 0.015 to 0.100 mg/mL [43]. Additionally, Yin-Fang Yan showed in his work that ethanolic extracts of H. lupulus showed moderate antifungal activity against pathogenic fungi, while isoxanthohumol, an isoprene flavonoid from H. lupulus, showed high antifungal activity, in particular against B. cinerea.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…Hops are a major source of phenolic compounds, and numerous animal and clinical experiments have asserted that the antioxidant properties of hops are related to the beneficial effects of their polyphenols [22]. Among the hop prenylflavonoids, XN and IX have been shown to have significant antioxidant potential [55][56][57][58]. The direct radical scavenging ability of XN and IX varies depending on the experimental methods.…”
Section: Hop and Its Major Components Xn And IX Decrease Fd-induced O...mentioning
confidence: 99%